Vulnerability Evolution of Coastal Erosion in the Pearl River Estuary Great Bay Area Due to the Influence of Human Activities in the Past Forty Years - Cao, Chao; Zhu, Kai; Cai, Feng; Qi, Hongshuai; Liu, Jianhui; Lei, Gang; Mao, Zijian; Zhao, Shaohua; Liu, Gen; Su, Yan (Frontiers in Marine Science, 2022)
Under the dual effects of global climate change and intensive human development activities, vulnerability to coastal erosion in bay areas is becoming increasingly serious. This study focuses on 15 counties and districts along the coast of the Pearl River Estuary (PRE) Great Bay Area and selects 12 evaluation indices from five perspectives for analysis, including coastal characteristics, hydrodynamic forces, economics, population and coastal reconstruction. The analytic hierarchy process (AHP) method, Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) method, independent weight method, Jenks natural breaks method (Jenks), exposure-sensitivity-adaptation (ESA) model and obstacle degree method are used in conjunction with the above indices to construct a coastal erosion vulnerability evaluation system for the PRE. The results show that coastal erosion vulnerability in the PRE is low in the eastern hilly area and high in the central and western delta areas. Coastal characteristics, coastal lowlands and protection capability are the main controlling elements of erosion. The PRE experienced an era of rapid economic development from 1980 to 2010, and coastal erosion vulnerability gradually increased, with a cost of ecological environment destruction. Then, an era of coastal zone ecological restoration supported by policy protection occurred from 2010 to 2020. Compared with three major bay areas with similar developed economies worldwide, the PRE is characterized by comparatively late but rapid economic development. Notably, the development and utilization efficiency of coastal zones is very high, the duration of damage to the ecological environment is short, and the effects of ecological repair and restoration are obvious. The results of this study provide a reference for economic development and ecological restoration in the bay areas of China and provide scientific guidance for coastal zone development, management and planning.